Plan de negocios distribuidora de frutas y verduras Cosechamos Colombia (2017)
The purpose of this document was to create a business plan of a fruit and vegetable distributor in Bogotá, Colombia. From a perspective that contributes to the nutritional development of the Colombian population in a safe, practical and pleasant way; promoting the consumption of fruits and vegetables and maintaining a healthy diet, through a product that is integral in quality, practicality and safety for consumption. The target market is people living in Bogota, stratum 3,4,5 and 6, who are interested in maintaining a healthy diet and has not been able to do because of the lack of time for the preparation of these foods. It was concluded, that the product offered by Cosechamos Colombia, is a development of an integral product in quality, practicality and security for consumption being fruits and vegetables 100% organic washed, peeled and cut; chosen by the clients themselves, fulfilling the promise of value of the objective of the business. And fundamentally, it can be recognized that it is a viable and profitable business, and can be implemented effectively, generating economic benefits to the company.